The Maintenance of Striped Catfish (Pangasius hypopthalumus) With Bioflocs Technology on Peat Swamp Water - Darmawan '; Rusliadi '; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from August until September 2016 at Laboratory Aquacultureof Technology Faculty Fisheries and Marine Science, University of Riau. The purpose of thisresearch was to investigate growth and survival rate of striped catfish with bioflocs system onpeat swamp water. This research using experimental method and completely random design(RAL) one factor with three treatment there are P0: without giving probiotics (control), P1:probiotics giving 5 ml/m3, P2: probiotics giving 10 ml/m3, P3: probiotics giving 15 ml/m3.The result showed that maintenance of striped catfish with bioflocs technology on peatswamp water is different giving affect significantly on the growth of absolute weight,absolute length growth, specific growth rate and food conversation rate (FCR), but not affectsignificantly on the survival rate, food efficiency. The best treatment were obtained intreatment three (P3) with probiotics dosage giving 15 ml/m3 with value growth of absoluteweight 10.49 gram, growth in absolute length 5.07 cm, specific growth rate 4.32 %, foodefficiency (EP) 98,38 %, food conversation rate (FCR) 1,03, flock volume 10.93 ml andsurvival rate 97.97 %.Keyword : striped catfish, bioflocs technology, peat swamp water